Mindfulness and Yoga - Meagan Arrastia-Chisholm; Katharine S. Adams; Huzeyfe Cakmakci; Teddi Cunningham (International Journal of Positivity & Well-Being, 2024)
More recently, counselors have been interested in mindfulness meditation and yoga practices. Although these practices may seem unconventional or alternative in some cultures, they actually fall under the umbrella of behavior therapy. Given the emphasis on skill building in behavior therapy, minfulness and yoga fit the the goal of reducingin distressing symptoms. To better understand these practices within the behavior therapy lens, this article reviews research concerning these interventions. Before synthesizing current trends in mindfulness meditation and yoga practices across contexts, we summarize the foundations and history of behavior therapy. Yoga, or physical activity, seems to be a great complement to Mindfulness Based Stress Reduction (MBSR) therapy, as well as Mindfulness-Based Cognitive Therapy (MBCT). Mindfulness-based approaches are effective in reducing depressive symptoms, anxiety, dysphoria, burnout, and rumination. Furthermore, these interventions support the social and emotional skills associated with self-regulation. Of course, the therapy chosen depends on the client’s goals and the therapist’s training experience. If the client wants these outcomes and is open to mediation and yoga, a counselor trained in these modalities should not hesitate to implement this facet of behavior therapy. Implications for helping clients increase wellbeing through skill building are offerred.